Homomorphisms between Pythagorean Multi Anti-Fuzzy Rings - Sadaqat Hussain; Zaheer Abbas; Muhammmad Yonus; Shamshad Ali; Yahya Khan; Iftikhar Hussain, (Dialogue Social Science Review (DSSR), 2025)
One of the important extensions of both the fuzzy set as well as the intuitionistic fuzzy set is the Pythagorean fuzzy sets which provides a flexible framework to deal with uncertainty and ambiguity. Rings are extensively studied within the modern algebra which helps in dealing with some complex problems of modern science and technology. In this article we propose the homomorphism between Pythagorean multi anti fuzzy rings. We also discuss some of its characteristics and use this construction to further study the image, pre image and some other properties of the homomorphism defined within this framework.